KNOWLEDGE AND PRACTICES OF PROFESSIONAL NURSES TOWARDS NURSES’ DOCUMENTATION AT KAYUNGA REGIONAL REFERRAL HOSPITAL, KAYUNGA DISTRICT. A CROSS-SECTIONAL STUDY. - Namulanda , Norah; Kyere, Olivia; Nansereko, Hasifa; Naggulu, Immaculate Prosperia; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2025)
Background Nurses’ documentation is a critical aspect of healthcare that ensures continuity of care, patient safety, and effective communication among healthcare professionals. However, gaps in knowledge and inadequate documentation practices compromise patient outcomes and legal compliance. This study aimed to assess the knowledge and practices of professional nurses regarding nurses' documentation at Kayunga Regional Referral Hospital, Kayunga District. Methodology The method was a descriptive cross-sectional study design using quantitative research methods. A structured questionnaire was administered, and a checklist for the practice of professional nurses at Kayunga Regional Referral Hospital was selected through purposive sampling. Data was collected on nurses' knowledge and practices regarding documentation and analyzed using descriptive statistics, with results presented in tables, pie charts, and figures. Results 60% of nurses had adequate knowledge of the importance of documentation, 55% were unaware of the potential consequences of improper documentation, and 53% did not consistently document nursing interventions provided to patients. 78% of nurses practiced real-time or near-real-time documentation, while 68% adhered to standardized documentation protocols. 22 (55%) were between 25 and 44 years old, while the least number of respondents, 2 (5%), were less than 25 years old. The majority, 32 (80%), were female, while the smallest group, 8 (20%), were males. 28 (70%) had attained a certificate in nursing, while the lowest number of respondents, 2 (5%), had attained a diploma in nursing. 24 (60%), had practiced for 1- 5 years, while the smallest group, 2 (5%), had practiced for less than 1 year Conclusion The study revealed that nurses understood the importance of documentation but struggled with applying documentation standards in practice. Recommendation The study recommended regular training, the use of structured formats, and real-time documentation to improve the quality and accuracy of nursing documentation at Kayunga Regional Referral Hospital.